New insights in animal models of neurotoxicity-induced neurodegeneration - Sanfeliu, Coral; Bartra, Clara; Suñol, Cristina; Rodríguez-Farré, Eduard (Frontiers in Neuroscience, 2024)
The high prevalence of neurodegenerative diseases is a consequence of the high longevity of the population, together with the lack of preventive and therapeutic options. There is great pressure on preclinical research, and both old and new models of neurodegenerative diseases are required to increase the pipeline of new drugs for clinical testing. We review the main models of neurotoxicity-based animal models leading to central neurodegeneration. Our main focus was on studying how changes in neurotransmission and neuroinflammation, mainly in rodent models, contribute to neurodegeneration . Most assays currently in use model the two most prevalent neurodegenerative diseases in the elderly population, Alzheimer's disease (AD) and Parkinson's disease (PD). AD is the most common age-related dementia, whereas PD is the most common movement disorder. Several neurotoxicants induce dopaminergic neurodegeneration and reproduce neuropathological traits of PD. The literature analysis of MPTP, 6-OH-dopamine and rotenone models, suggested the later as a useful model when specific doses of rotenone were administrated to C57BL/6 mice. Cholinergic neurodegeneration is mainly modelled with the toxin scopolamine, which is a useful model for the screening of protective drugs against cognitive decline and AD. Several agents have been used to model neuroinflammation-based neurodegeneration and dementia in AD, including lipopolysaccharide (LPS), streptozotocin and monomeric C-reactive protein. The bacterial agent LPS makes a useful model for testing anti-inflammatory therapies to halt the development and severity of AD. However, whereas neurotoxin models might be more useful than genetic models for drug discovery in PD that is not the case in AD.